2023
DOI: 10.1108/jgm-09-2022-0050
|View full text |Cite
|
Sign up to set email alerts
|

The evolving field of global mobility: responses to global volatility (2013–2022)

Abstract: PurposeA decade has passed since Dabic et al. (2015) published a systematic review of the evolution of the expatriate literature from 1970 to 2012. Moreover, the past five years have been turbulent, with many global crises affecting organizational approaches to the global movement of people, particularly expatriate workers. Thus, this article seeks to understand how global mobility has continued to evolve during such turbulence and propose avenues for future research.Design/methodology/approachIn this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Recent research has observed long-term mental health concerns for those who have had COVID-19 (Reskati et al, 2023;Badinlou et al, 2022;Matsumoto et al, 2022). Therefore, with IAs continuing to be utilized at levels equal to or greater than pre-COVID times (Ridgway and Langinier, 2023), in addition to mental health challenges, the onslaught of COVID-19 can also be termed as a significant external circumstance that has further exacerbated expatriates' psychological adjustment (Tripathi and Singh, 2021). However, very little empirical research is available on how COVID-19 has further exacerbated expatriates' mental health challenges when sent on IAs and how their concerns relating to their psychological adjustment to the host country can be addressed (Sahoo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has observed long-term mental health concerns for those who have had COVID-19 (Reskati et al, 2023;Badinlou et al, 2022;Matsumoto et al, 2022). Therefore, with IAs continuing to be utilized at levels equal to or greater than pre-COVID times (Ridgway and Langinier, 2023), in addition to mental health challenges, the onslaught of COVID-19 can also be termed as a significant external circumstance that has further exacerbated expatriates' psychological adjustment (Tripathi and Singh, 2021). However, very little empirical research is available on how COVID-19 has further exacerbated expatriates' mental health challenges when sent on IAs and how their concerns relating to their psychological adjustment to the host country can be addressed (Sahoo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…International assignments (IAs) are growing exponentially (Ridgway and Langinier, 2023). Multinational enterprises (MNE) utilization of expatriates (expats) requires a comprehensive IHRM strategy that is informed, in part, by a complex understanding of the facets that impact an expatriate's psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%